Loading natural emulsions with nutraceuticals using the pH-driven method: formation & stability of curcumin-loaded soybean oil bodies. Issue 9 (14th August 2019) - Zheng, Bingjing; Zhang, Xiaoyun; Lin, Helen; McClements, David Julian
Abstract : The pH-driven method was used to load curcumin into soymilk. The soymilk had good physical stability but curcumin degradation occurred at higher storage temperatures. Abstract : Previous studies have shown that the pH-driven method can be used to load curcumin into a variety of colloidal particles, including micelles, liposomes, lipid droplets, and oil bodies. This method is based on the increase in hydrophobicity and a corresponding decrease in water-solubility of curcumin when the pH changes from highly alkaline to acidic. In this study, we examined the physical and chemical stability of curcumin-loaded soybean oil bodies prepared using the pH-driven method. First, the impact of pH (from 6.5 to 8) on the stability of curcumin-loaded soymilk during storage was investigated at 4 °C for 36 days. At this low storage temperature, more than 85% of the alkaline-sensitive curcumin was retained at all three pH values, without any evidence of color fading. The impact of holding temperature (4, 20, 37, and 55 °C) on the physicochemical stability of the curcumin-loaded soymilks was then measured during storage at pH 7 for 14 days. At 4 and 20 °C, the emulsions remained physically stable, most of the curcumin (>90%) was retained, and there was no evidence of color fading. At the higher temperatures, however, the rate of curcumin degradation increased. For instance, around 30% and 70% of curcumin was lost when the soymilks were stored at 37 and 55 °C, respectively. On the other hand, the soymilks remained physically stable throughout this period. This study provides valuable information about the loading of curcumin into pre-existing plant-based milks and creamers, which may be useful for developing a new category of functional foods and beverages.